Systematic review of structural interventions for intimate partner violence in low- and middle-income countries: organizing evidence for prevention. (December 2015) - Bourey, Christine; Williams, Whitney; Bernstein, Erin; Stephenson, Rob
Abstract Background Despite growing attention to intimate partner violence (IPV) globally, systematic evaluation of evidence for IPV prevention remains limited. This particularly is true in relation to low- and middle-income countries (LMIC), where researchers often organize evidence by current interventions strategies rather than comprehensive models of IPV. Applying the concept of structural interventions to IPV, we systematically reviewed the quantitative impact of such interventions for prevention of male-to-female IPV in LMIC in order to (a) highlight current opportunities for IPV research and programming and (b) demonstrate how structural interventions may provide an organizing framework through which to build an evidence base for IPV prevention. Methods We identified articles by systematically searching PubMed and Web of Science, reviewing references of selected studies, and contacting 23 experts. Inclusion criteria included original research, written in English, published between January 2000 and May 2015 in the peer-reviewed literature. Studies evaluated the quantitative impact of structural interventions for the prevention of male-to-female IPV in LMIC through (a) IPV incidence or prevalence or (b) secondary outcomes theoretically linked to IPV by study authors. After initial screening, we evaluated full text articles for inclusion and extracted data on study characteristics, outcomes, and risk of bias, using forms developed for the review. Results Twenty articles (16 studies) from nine countries met inclusion criteria, representing 13 randomized control trials and seven additional studies, all of which reported results from economic, social, or combined economic and social interventions. Standardized atp < 0.05 or 95 % confidence intervals not including unity, 13 studies demonstrated statistically significant effects for at least one primary or secondary outcome, including decreased IPV and controlling behaviors; improved economic wellbeing; enhanced relationship quality, empowerment, or social capital; reduced acceptability of IPV; new help seeking behaviors; and more equitable gender norms. Risk of bias, however, varied in meaningful ways. Conclusions Our findings support the potential effectiveness of structural interventions for IPV prevention. Structural interventions, as an organizing framework, may advance IPV prevention by consolidating available evidence; highlighting opportunities to assess a broader range of interventions, including politico-legal and physical approaches; and emphasizing opportunities to improve evaluation of such interventions.